Charles B. McVay papers - McVay, Charles B. (Charles Butler), 1868-1949.
Correspondence, speech, writings, newspaper clippings, printed matter, photographs, and other papers relating chiefly to McVay's duties as commander-in-chief of the U.S. Navy Asiatic Fleet in 1929 and 1930. Correspondents include Charles Francis Adams, William R. Castle, Edwin Sheddan Cunningham, Dwight Filley Davis, Lynn Winterdale Franklin, Nelson T. Johnson, and Howard Charles Kelly.
Naval officer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Forms part of: Naval Historical Foundation collection.
Keywords: Adams, Charles Francis, -- 1866-1954 -- Correspondence; Castle, William R. -- 1878-1963 -- Correspondence; Cunningham, Edwin Sheddan, -- 1868-1953 -- Correspondence; Davis, Dwight Filley, -- 1879-1945 -- Correspondence; Franklin, Lynn Winterdale, -- 1888-1952 -- Correspondence; Johnson, Nelson T. -- 1887-1954 -- Correspondence; Kelly, Howard Charles, -- 1887-1952 -- Correspondence; United States. -- Navy. -- Asiatic Fleet; United States. -- Navy -- Foreign service -- Pacific Area; Naval officers